A propòsit de «Poetes universitaris valencians» - Carbó, Ferran (Caplletra. Revista Internacional de Filologia, 2015)
The post-war poetry has often been divided in several groups added to the updated anthologies. In 1962 Poetes universitaris valencians appeared and a group of young writers were added to the already known ones from the sixties. The anthology and the writers’ developement are reviewed in this paper.